2009
DOI: 10.1093/ntr/ntp056
|View full text |Cite
|
Sign up to set email alerts
|

Increasing smoking cessation care provision in hospitals: A meta-analysis of intervention effect

Abstract: Interventions can be effective in increasing the routine provision of hospital smoking cessation care. Future research should use more rigorous study design, examine a broader range of smoking cessation care practices, and focus on hospital-wide intervention implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 69 publications
(141 reference statements)
1
45
0
Order By: Relevance
“…A lack of insight from patient perspectives in hospitals with smokefree grounds policies hinders our ability to both enhance health outcomes of patients addicted to nicotine [14,15] and to achieve policy compliance of smoke-free grounds [20]. Studies in health care settings have reported that tobacco dependence treatment continues to be inadequate [2][3][4][5], even though smoking bans have become increasingly stricter. Patients who self-identified as current and former smokers highlighted the inadequate treatment for their tobacco dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of insight from patient perspectives in hospitals with smokefree grounds policies hinders our ability to both enhance health outcomes of patients addicted to nicotine [14,15] and to achieve policy compliance of smoke-free grounds [20]. Studies in health care settings have reported that tobacco dependence treatment continues to be inadequate [2][3][4][5], even though smoking bans have become increasingly stricter. Patients who self-identified as current and former smokers highlighted the inadequate treatment for their tobacco dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goals of second-hand smoke exposure protection and denormalization messages are joined with the anticipation of reducing or eliminating tobacco use among patients, staff and visitors [1]. In acute care hospitals with smokefree building restrictions, research suggests that tobacco dependence treatment is either inconsistently offered or not present [2][3][4][5]. Additionally, in hospitals with smoke-free grounds policy, evidence suggests that noncompliance is a persistent issue [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16)(17)(18)(19) Even simple interventions, without previous planning and with an emphasis on motivation for smoking cessation, show favorable results. (20,21) However, it should be borne in mind that smoking cessation is multifactorial (9,14,(22)(23)(24)(25)(26)(27) and is often hindered by factors unrelated to physician intervention. (28) In addition to physician intervention, there are pharmacological treatments that assist patients in smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professional advice to quit smoking has been shown to be effective at reducing the levels of smoking amongst patients [5,6,7], particularly if followed up with further support [8,9]. Hospitalised patient populations may be highly receptive to such advice, for example one large study revealed as many as 75% of cardiac in-patient smokers are prepared to quit [10].…”
Section: Introductionmentioning
confidence: 99%